El juego dirigido en el desarrollo del esquema corporal de los niños del subnivel II, de la Unidad Educativa Quislag, de la comunidad Quislag, parroquia Tixán, provincia de Chimborazo, período octubre 2020 – marzo 2021 - Riera Cobos, Karen Pamela (2021)
This investigation work was carried out in the “Quislag” Educational Unit, it belongs to the Quislag community, Tixán parish, Alausí canton. The general objective was to determine the incidence of directed games in the development of the body schema of children in sublevel II. According to the specific objectives set, different games to be applied in this area and their usefulness were identified, in addition there was a theoretical basis in order to understand the variables. The methodology used is descriptive, bibliographic and on field, with inductive methods, analytical synthetic deductive, in addition techniques such as the survey aimed to the teachers of the educational unit and its instrument the questionnaire of questions related to the subject are implemented. The main results were obtained after the applied diagnosis and it was that the highest percentage of teachers are not carrying out activities in which the child manages to develop their body scheme. It is concluded that the development of the body expression of boys and girls is a pedagogical resource of great efficiency and an excellent option for the development of their behavior, personality, physical and intellectual capacity. It is recommended to work through body expression since it helps to organize movements autonomously and on their own initiative, for their development, in addition to following the proposed activities.